Cervical Ganglioneuroma. A Pediatric Case Presentation and Review of the Literature - Mányeles Brito Vázquez; Yamila Muga Baluja; José Miguel Alcalde Rojas (Revista Finlay)
The ganglioneuroma is a benign primitive neuroectodermal tumor, which derives from the ganglia of the sympathetic system and is composed of mature Schwann cells, ganglion cells, and nerve fibers. A rare neck tumor, in a female pediatric patient with a history of cervical tumor mass for two years is presented. In the imaging studies performed, a heterogeneous solid lesion with punctate calcifications was diagnosed, compressing adjacent bone and vascular structures. To obtain histology, an ultrasound-guided core needle biopsy was performed, and the diagnosis of cervical ganglioneuroma was informed by pathological anatomy. Due to the low incidence of ganglioneuroma as a tumor variety, and in turn, the rare cervical location in a small percentage of patients, the present research aims to enrich the national and international scientific literature, providing a new case that serves as the basis for future research, respecting the ethical principles of health research.